2018
DOI: 10.1002/jsfa.9157
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of the factors that determine the activity of the rumen microbiota for further applications as inoculum

Abstract: Fresh rumen fluid sampled at 3 h after feeding from donor animals that were fed concentrate diets should be chosen when the aim is to provide the most diverse and active rumen microbial inoculum. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 53 publications
3
9
0
Order By: Relevance
“…The freeze-drying process produced the lowest fermentation activity and a very poor relation with fresh liquid among feeds, confirming similar findings obtained by Belanche et al [9]. Several methodological factors can explain these poor results, such as the absence of cryoprotectants, the procedure of pellet preparation in terms of centrifugation intensity, and an improper process of rehydration.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The freeze-drying process produced the lowest fermentation activity and a very poor relation with fresh liquid among feeds, confirming similar findings obtained by Belanche et al [9]. Several methodological factors can explain these poor results, such as the absence of cryoprotectants, the procedure of pellet preparation in terms of centrifugation intensity, and an improper process of rehydration.…”
Section: Discussionsupporting
confidence: 87%
“…The protection of the microbiota from freezing damage can be obtained by adding organic chemicals with cryoprotectant properties but these compounds can interfere with the subsequent in vitro tests because they are fermentable substrates (e.g., glycerol, [12]) or can have toxic effects (e.g., dimethyl sulfoxide). A possible improvement of our chilling procedure [9,12] could be to avoid freezing large amounts of inoculum and to divide it into small amounts (e.g., 30–50 mL) because the high surface/volume accelerates the freezing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study two types of fresh rumen inocula, along with autoclaved inocula, were used to test whether the microbes (or their fermentation products) could affect rumen microbial colonization in early life as previously suggested [20,21]. In an earlier in vitro study we evaluated the microbial activity of different types of rumen inocula, sampling time, and preservation methods and we concluded that fresh rumen uid sampled at 3 h after feeding provides the most diverse and active inoculum [18]. The present in vivo study builds upon these observations to gain insight in the microbiological processes occurring in the rumen.…”
Section: Discussionmentioning
confidence: 90%
“…In previous works, we optimized the type of inocula [18] and we showed [19] that early-in-life inoculation of goat kids with rumen uid from adult animals stimulated feed intake and rumen function in terms of volatile fatty acids (VFA) production during the pre-weaning period. This inoculation also helped the transition from liquid to solid feeding and to minimize the growth retardation following weaning.…”
Section: Introductionmentioning
confidence: 99%